NUMERICAL ENTROPY PRODUCTION OF THE ONE-AND-A-HALF-DIMENSIONAL SHALLOW WATER EQUATIONS WITH TOPOGRAPHY - Mungkasi, Sudi (Journal of the Indonesian Mathematical Society, 2015)
Numerical entropy production can be used as a smoothness indicator of solutions to conservation laws. By definition the entropy production is non-positive. However some authors, using a finite volume method framework, showed that positive overshoots of the numerical entropy production were possible for conservation laws (no source terms involved). Note that the one-and-a-half-dimensional shallow water equations without source terms are conservation laws. A report has been published regarding the behaviour of the numerical entropy production of the one-and-a-half-dimensional shallow water equations without source terms. The main result of that report was that positive overshoots of the numerical entropy production were avoided by use of a modified entropy flux which satisfies a discrete numerical entropy inequality. In the present article we consider an extension problem of the previous report. We take the one-and-a-half-dimensional shallow water equations involving topography. The topography is a source term in the considered system of equations. Our results confirm that a modified entropy flux which satisfies a discrete numerical entropy inequality is indeed required to have no positive overshoots of the entropy production.DOI :Â http://dx.doi.org/10.22342/jims.21.1.198.35-43